In a queer time and place: Transgender bodies, subcultural lives - Halberstam, Jack (J.) (New York University Press, 2005)
In a Queer Time and Place opens with a probing analysis of the life and death of Brandon Teena, a young transgender man who was brutally murdered in small-town Nebraska. After looking at mainstream representations of the transgender body as exhibited in the media frenzy surrounding this highly visible case and the Oscar-winning film based on Brandon's story, Boys Don’t Cry, Halberstam turns her attention to the cultural and artistic production of queers themselves. Halberstam examines the “transgender gaze,” as rendered in small art-house films like By Hook or By Crook, as well as figurations of ambiguous embodiment in the art of Del LaGrace Volcano, Jenny Saville, Eva Hesse, Shirin Neshat, and others. Halberstam then exposes the influence of lesbian drag king cultures upon hetero-male comic films, such as Austin Powers and The Full Monty, and, finally, points to dyke subcultures as one site for the development of queer counterpublics and queer temporalities. Considering the sudden visibility of the transgender body in the early twenty-first century against the backdrop of changing conceptions of space and time, In a Queer Time and Place is the first full-length study of transgender representations in art, fiction, film, video, and music. This pioneering book offers both a jumping off point for future analysis of transgenderism and an important new way to understand cultural constructions of time and place.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; cinéma; communication; cours; discipline; fem1000; har4600; identités LGBTQIA2+; lit4700; personnes trans*; premier cycle; périodes historiques; queer; régions géographiques; thématiques; transféminisme; états-unis; études culturelles

Avoir l’air butch. Une esquisse de guide sur les butches au cinéma. Partie 1/2 - Halberstam, Jack (Genre en séries, 2019)
Nous proposons ici la première partie de ce chapitre. La partie 2 sera publiée dans le prochain numéro de Genre en séries : cinéma, télévision, cinéma. Le prénom Jack a été choisi ici parce que Halberstam tend à le privilégier depuis ses recherches sur les drag kings (http://www.lambdaliterary.org/interviews/02/01/jack-halberstam-queers-create-better-models-of-success/), tout en insistant sur sa volonté de ne pas résoudre son ambiguïté genrée (« my floating gender pronouns capture well the refusal to resolve my gender ambiguity that has become a kind of identity for me »). Voir http://www.jackhalberstam.com/on-pronouns/
Keywords: 1900-1999; amériques; approches et analyses; cinéma; communication; discipline; hétérosexisme; identités LGBTQIA2+; périodes historiques; queer; ressource en ligne; régions géographiques; systèmes d'oppressions; états-unis